How to research trends move beyond trend watching to kickstart innovation - Dragt, Els (BIS Publishers, 2017)
Understanding trends, the emerging values and needs of groups in society provides you with a foundation to innovate and create change. This book gives you an overview of the trend research process. lt brings a structured, research-based approach to the table instead of a crystal ball. It is practical, hands-on and offers multiple perspectives on researching trends for professionals and trend students around the globe. lt shows you that researching trends is a skill that combines the intuitive and the analytical. Based on a 3 step method, you will learn in a hands-on way to scan your environment for signs of change, analyse your trend spots and apply your trend insights to kick start innovation. This book synthesises existing theories, concepts and ideas on trend research. The interviews with experts and students will guide you on your trend journey.--Publisher